Rebuilding the Province under the Sign of the Divinity. Tegulae with Christian Symbols from the Province of Scythia - Radu Petcu (Frontière·s)
This study examines the incorporation of Christian symbolism into architectural materials, particularly tegulae (roof tiles and bricks), in the Roman province of Scythia during the period of Late Antiquity (5th-6th centuries CE). Drawing on seventeen artefacts discovered at nine sites, we analyze the distribution, typology and iconographic function of Christian symbols, including crosses, monograms and images of saints, on building materials used in domestic, ecclesiastical, funerary and military contexts. These symbols served both spiritual and protective purposes and were closely associated with the Christianization of urban spaces and imperial ideology. The presence of imperial inscriptions, notably those of Emperor Anastasius, further illustrates the fusion of political and religious authority. Situating the material from Scythia within the broader Eastern Roman world highlights the shared spiritual and architectural transformations that characterized the late antique Christian empire.